2014
DOI: 10.9790/3013-040417-23
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Adverse Drug Reactions: Evaluations of Knowledge, Attitude and Practice among Community Pharmacists in UAE

Abstract: : In United Arab Emirates (UAE), the pharmacovigilance (PV) program is in the stage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
5
20
1
Order By: Relevance
“…The study findings have demonstrated that the community pharmacists possess a positive attitude toward ADR reporting, although the majority of them never reported any ADRs. In a study conducted by Cheema et al in London observed in their study "Community Pharmacist-Led New Medicines Service for patients with long-term medical condition -A cross-sectional study has revealed that ADR reporting has identified new service by community pharmacists to be offered to the patients voluntarily to identify potential ADRs that lead to increased morbidity in patients with chronic diseases not only improves patients health but also the reputation to the pharmacist [13] that similar findings were also observed in the studies conducted at United Arab Emirates and Malaysia with respect to the positive attitude of the community pharmacists in reporting ADRs in the community*pharmacy settings [12,14,15].…”
Section: Srikanth and Adepumentioning
confidence: 76%
See 1 more Smart Citation
“…The study findings have demonstrated that the community pharmacists possess a positive attitude toward ADR reporting, although the majority of them never reported any ADRs. In a study conducted by Cheema et al in London observed in their study "Community Pharmacist-Led New Medicines Service for patients with long-term medical condition -A cross-sectional study has revealed that ADR reporting has identified new service by community pharmacists to be offered to the patients voluntarily to identify potential ADRs that lead to increased morbidity in patients with chronic diseases not only improves patients health but also the reputation to the pharmacist [13] that similar findings were also observed in the studies conducted at United Arab Emirates and Malaysia with respect to the positive attitude of the community pharmacists in reporting ADRs in the community*pharmacy settings [12,14,15].…”
Section: Srikanth and Adepumentioning
confidence: 76%
“…The findings suggest that the knowledge component score of the participants has increased from pre-training test score of 4.87±2.01 to post-test score of 7.09±0.68, which is a significant improvement (p<0.001) suggesting the influential role of training on exit-level knowledge of the participants. Findings of various studies regarding assessment of KAP of pharmacists toward ADR reporting suggest that pharmacists have inadequate knowledge regarding ADRs, predisposing factors and reporting of ADRs [15].…”
Section: Srikanth and Adepumentioning
confidence: 99%
“…Many studies included in this review lacked a theoretical framework. In papers in which a theoretical framework was utilized, Inmans’ seven deadly sins for not reporting ADEs; Knowledge‐Attitude‐Practice Model (KAP); and theory of planned behaviour were the most frequently used theories to understand pharmacists' reporting of ADEs …”
Section: Resultsmentioning
confidence: 99%
“…[24,[36][37][38] Many studies included in this review lacked a theoretical framework. In papers in which a theoretical framework was utilized, Inmans' seven deadly sins for not reporting ADEs [32,33,35,39,40] ; Knowledge-Attitude-Practice Model (KAP) [29][30][31]34,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] ; and theory of planned behaviour were the most frequently used theories to understand pharmacists' reporting of ADEs. [57] reporting [58] and knowledge [59] of ADEs in two studies.…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
“…On the other hand, community pharmacists in Netherland were actively participating in ADR reporting and considered it as a legal implication toward their profession [20]. Community pharmacists from UAE and Hong Kong showed positive attitude toward ADR reporting though they had poor knowledge and awareness regarding ADR reporting system and pharmacovigilance activities, which probably might be the cause of under-reporting of ADRs [21,22].…”
Section: Adr Monitoring Trends In Developed Countriesmentioning
confidence: 99%